The Influence of Tax Literacy, Tax Sanctions, and Tax Culture on the Tax Compliance of Regional Government Apparatus: The Moderating Role of Tax Digitalization in Bolaang Mongondow Regency - Ani, Ani Putri; Jullie Jeannete Sondakh; Stenly Kho Walandouw (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Tax compliance among regional government apparatus is a crucial aspect in supporting accountable and administratively orderly regional financial management. However, in practice, compliance issues are still observed, influenced by variations in tax literacy levels among officials, the implementation of tax sanctions, organizational culture, and the utilization of tax digitalization systems. This condition indicates a gap between officials’ understanding and the optimal use of technology in supporting tax compliance. This study aims to analyze the influence of tax literacy, tax sanctions, and tax culture on the tax compliance of regional government apparatus, as well as to examine the moderating role of tax digitalization in the relationship between tax literacy, tax sanctions, and tax culture and tax compliance in Bolaang Mongondow Regency. This study employs a quantitative approach using a survey method by distributing questionnaires to financial and tax management officials within regional government agencies. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that tax literacy, tax sanctions, tax culture, and tax digitalization significantly influence tax compliance among regional government apparatus. However, tax digitalization does not moderate the relationship between tax literacy, tax sanctions, and tax culture and tax compliance. Compliance among officials is more strongly influenced by awareness of legal consequences, organizational values, and administrative mechanisms rather than by the utilization of technology. Furthermore, the uneven implementation of digital systems, limited infrastructure, differences in officials’ capabilities in operating applications, and the predominantly administrative function of technology contribute to the inability of digitalization to strengthen the relationship between behavioral factors and tax compliance. This study emphasizes the importance of enhancing officials’ competencies, organizational support, and infrastructure to ensure that digital transformation can effectively improve tax compliance.